Epidural pressure and brain tissue pH in the rat main cerebral artery embolization model - Yamane, Kanji; Uozumi, Tohru; Okada, Yoshikazu; Takeda, Tetsuji; Shima, Takeshi (Japanese Journal of Stroke, 1990)
The purpose of this study was to investigate acute brain edema in the embolized rats by measuring epidural pressure (EDP) and evaluating brain tissue pH. Thirty five male Wistar rats, aged from 20 to 25 weeks, were used. Under light anesthesia with halothane, cerebral artery was occluded with silicone cylinder embolus through the cervical internal carotid artery. EDP was measured with our specially designed microballoon applied at the parietal region within 5 hours after embolization. Changes in brain tissue pH were evaluated after recordig of EDP with umbelliferone method. To evaluate blood-brain barrier (BBB) function, 0.4 ml of 1% Evans blue was injected intraveously 30 min before sacrifice. Changes in EDP were varied from animal to animal, ranging from 0 to 70 mmHg (26.6 ± 22.4 mmHg, mean ± SD, n=27). Characteristic acute brain swelling was detected in the rat with drastic increase in EDP. Brain tissue pH demonstrated acidotic changes in the cortex and caudate putamen, and heterogeneous changes including alkalosis and acidosis in the deep cerebrum (i.e. hippocampus, thalamus, and hypothalamus). The alkalotic area was corresponding well with the Evans blue exudated area. Further, the degree of EDP elevation was correlated well with the size of alkalotic area (y=0.73x + 0.63, r=0.81), not with acidotic area. This study demonstrated the rat main cerebral artery embolization developed ischemic brain swellig with prominent EDP increase in the deep cerebrum due to vasogenic edema.